Výsledky a komplikace po operačním řešení LSS v horizontu jednoho roku – prospektivní studie - Ježek, J; Waldauf, P; Krbec, M; Douša, P; Skála-Rosenbaum, J (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY Lumbar spinal stenosis (LSS) is a serious and fairly frequent disorder with prevalence increasing with age which often results in a disability. The surgical procedures are often very risky due to the greater age of patients with severe stenosis and their comorbidities. The study aimed to assess the functional outcomes and complications in patients who underwent surgical treatment for LSS at one year postoperatively and to identify the differences in the functional outcomes, if any, in dependence on the number of operated segments. MATERIAL AND METHODS It was a prospective study which included 33 patients who underwent surgery at the authors department from 1 November 2015 to 1 October 2016 for LSS, the mean age of patients was 69.5 (43-83) years. The surgery was indicated based on the clinical examination, radiography and MR imaging and consisted in posterior decompression with or without stabilisation and fusion. Pre- and post-operatively, a neurological examination and evaluation of patient difficulties were performed by: VAS - particularly for low back pain (VAS-LB) and lower limb pain (VAS-LL), Oswestry Disability Index (ODI) and Swiss Spinal Stenosis Questionnaire (SSSQ). The evaluation was done at a half year and one year after the surgery. The authors made comparisons in dependence on the number of treated segments (1-2, 3-5 and Th-S stabilisation). RESULTS A significant improvement of all the followed-up parameters was reported at one year postoperatively. At one year after the surgery, the VAS-LB score showed a decrease by 2.39 (p = 0.001), the VAS-LL by 3.26 (p < 0.001), while a decrease by 2 or more points is considered clinically significant. When evaluating the SSSQ questionnaire, a decrease in subjective difficulties (SSSQ-S) was by 0.89 (p < 0.001), in physical function (SSSQ-F) by 0.87 (p < 0.001). In this questionnaire, the satisfaction rate with the surgery was 2 - i.e. somewhat satisfied. Altogether 76% of patients were very or somewhat satisfied, no one was very dissatisfied. When evaluating the ODI, an improvement by 20.6% (p < 0.001) was reported. The authors identified neither any significant differences in the outcomes at a one-year follow-up in dependence on the length of stabilisation, nor any significant differences between the six-months and one-year follow-up. Intraoperative complications occurred in 18%, early postoperative complications in 6% of patients. The ASD developed in 9% within one year. DISCUSSION The authors confirmed a significant improvement of the followed-up parameters (VAS-LB, VAS-LL, SSSQ, ODI) which corresponds with recent literature. The decrease in VAS and ODI in the authors study is more marked than the outcomes stated in literature. The authors outcomes clearly show that there is no correlation with the length of stabilisation and the number of decompressed segments. Conversely, the rate of complications was higher in this group than the rates stated in literature, but majority of complications had no consequences for the patients. CONCLUSIONS In the group of patients with a one-year follow-up the authors confirmed that surgical procedures will result in reduced subjective difficulties of patients, reduced pain and improvement of physical function. A significant improvement of all the followed-up parameters was reported. The authors did not confirm the correlation between the postoperative improvement and the number of treated segments. Key words:lumbar spinal stenosis, quality of life, post-operative outcomes, complications.
Keywords: Surveys and Questionnaires; chirurgická dekomprese; Disability Evaluation; Patient Satisfaction; Spinal Stenosis; Humans; lidé středního věku; Spinal Fusion; spinální stenóza; Lumbar Vertebrae; posuzování pracovní neschopnosti; Quality of Life; Aged; dospělí; výsledek terapie; senioři; lidé; obnova funkce; spokojenost pacientů; kvalita života; průzkumy a dotazníky; bederní obratle; Adult; Follow-Up Studies; Middle Aged; Recovery of Function; Treatment Outcome; Aged, 80 and over; senioři nad 80 let; fúze páteře; prospektivní studie; Decompression, Surgical; následné studie; Prospective Studies